Development of Integrated Warehouse Application for Retail Business with Multi-Echelon Demand using Open-source ERP System - Prita Meilanitasari; Muhammad Faisal Ibrahim (Jurnal Sistem Informasi, 2023)
The Integrated Warehouse Application (IWA) is a platform that combines inventory management, order management, warehouse operations, shipping, logistics, and reporting and analysis. It helps users manage their inventory to meet supply and demand requirements. Although many large companies use IWA to increase their operational efficiency, its complexity, technology, and customization requirements make it too expensive for small and medium-sized enterprises (SMEs). Our study focuses on SMEs in the retail business, where fast and accurate order processing is important for customer satisfaction and loyalty. We researched how to accommodate multi-echelon demand for the retail industry. To address these challenges, we used an Open-source ERP System called Odoo to create the IWA. Our findings show that implementing an integrated warehouse inventory system like the one provided by Odoo can offer real-time visibility into inventory levels, orders, and shipments. Automating manual processes enhances speed and accuracy, which improves customer service and business performance.